The use of matrix training to promote generative language with children with autism. Issue 4 (29th July 2016) - Frampton, Sarah E.; Wymer, Sarah C.; Hansen, Bethany; Shillingsburg, M. Alice
Abstract : Matrix training consists of planning instruction by arranging components of desired skills across 2 axes. After training with diagonal targets that each combine 2 unique skill components, responses to nondiagonal targets, consisting of novel combinations of the components, may emerge. A multiple‐probe design across participants was used to evaluate matrix training with known nouns (e.g., cat ) and verbs (e.g., jumping ) with 5 children with autism spectrum disorders (ASD). Following baseline of Matrix 1 and a generalization matrix, diagonal targets within Matrix 1 were trained as noun–verb combinations (e.g., cat jumping ). Posttests showed recombinative generalization within Matrix 1 and the generalization matrix for 4 participants. For 1 participant, diagonal training across multiple matrices was provided until correct responding was observed in the generalization matrix. Results support the use of matrix training to promote untrained responses for learners with ASD and offer a systematic way to evaluate the extent of generalization within and across matrices.